Pengaruh Latihan Kombinasi Terhadap Penurunan Risiko Jatuh Pada Lanjut Usia - Rindyastuty, Hutami; , Yulisna Mutia Sari SST.FT., M.Sc (GRS) (2017)
Background: The aging process in the elderly can generates some problems or regressions in many aspects, as in hysical, biological, psychological, spiritual, and even economics. Those things are most likely the reasons behind heincreasing risks of the elderly, like falling. Falling cannot be erestimated as it is one of the reasons of death and njuries for the elderly. The factors that are increasing the risk of falling can be the decreased of the balance controller, like reduction of muscle strengths, changes of posture, the mass of fat that is piling up on certain areas, reduced propioseptive, and visual. One of ways to reduce the risk of falling in the elderly is giving them the combined exercise, such as aerobic, stretching, and strengthening..The Objective of Research: To find out the effect of combined exercise towards the decreased risk of falling of the elderly in Posyandu Ngudi Sehat ColomaduThe Benefit of Research: To understand the effect of combined exercise in reducing the risk of faling in the elderlyThe Method of Research: This research uses the Quasy Experimental method. The sampling technique that is used is Purposive Sampling. The obtained sample based on the inclusion and exclusion criteria are 20 people. The measurement for the risk of falling before and after the exercise given uses The Tinetti Gait and Balance Instrument. The effect test uses the Wilcoxon test with p value is 0,000Result of the Research: The analysis of statistics was obtained by result base on the Wilcoxon test, it could be seen that p-value 0, 000< 0,005 so H0 is rejected and Hα is accepted. It can be interpreted that there is an effect of the combined exercise to the risk of falling in the elderly.Conclusion: Giving the combined exercise for four weeks is reducing the risk of falling in the elderly in Posyandu Ngudi Sehat Colomadu. Keywords: Risk of falling, combined exercise, The Tinetti Gait and Balance Instrument, elderly.